¿Why are women invisible in the Teaching of history? Abstract (2011)
In this article we wonder why women are invisible in the teaching of history and we develop some assumptions about the reasons for this invisibility. We analyze the place women occupy in the curriculum of social sciences and history of Catalonia to claim their presence in texts and in practices. We exemplify their role in a teaching unit called Gifts of the 36 -Women of the 36- dedicated to recall the role of Republican women during the Spanish Civil War, the Franquism and the transition to democracy.